EDUKASI KESEHATAN TENTANG PENCEGAHAN TUBERKULOSIS DI TABA MELINTANG WILAYAH KERJA PUSKESMAS BENTIRING - Nopia Wati; Hasan Husin; Agus Ramon (Sambulu Gana : Jurnal Pengabdian Masyarakat, 2022)
Tuberculosis is still a serious health problem both globally and locally. Tuberculosis control has been regulated in the Minister of Health regulation number 67 of 2016 including risk control, one of which is health promotion for prevention. Taba Melintang Working Area of ​​Bentiring Health Center has never had a health education program and as a support for the ministry of health program, community service was carried out in the form of health counseling for tuberculosis prevention. The community service method is carried out by the lecture method followed by a question and answer session with the target population of Taba Melintang. This community service will be held from October 11 to November 31, 2021. Before and after the counseling, residents are given a pre test and post test. The results show that there is a difference in the level of knowledge between before and after health education on tuberculosis prevention in Taba Melintang, Bentiring Health Center Work Area. Other activities carried out are free medical treatment for residents..